Efektifitas Konten Edukasi Tiktok Sebagai Instrumen Evaluasi Pembelajaran yang Adaptif dan Non-Monoton - Isti Koma; Aulia Tanzania; Riski Apriyansah; Amelia Handayani (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The shift in learning evaluation from conventional methods toward more dynamic instruments has become increasingly important in contemporary education. This study aims to analyze the effectiveness of using TikTok educational content as an adaptive and non-monotonous learning evaluation instrument. The research employs a descriptive qualitative method. The findings indicate that TikTok functions not only as a medium for delivering learning materials but also as an authentic assessment tool capable of enhancing students' creativity and engagement. The characteristics of short-form videos, editing features, and visual elements make TikTok an instrument that is highly adaptable to the learning styles of Generation Z students, thereby reducing boredom in formal evaluation processes.